(untitled) (Human Factors in Design, 2022)
Based on the theme of excessive use of smartphones, this research addresses, from a bibliographic review, related topics to causes and consequences of an addictive smartphone usage; and the design relationship - User Experience (UX), in particular - as a mediator of this process of consumption. Subsequently, through the methodology of Double Diamond, a proposal was developed to increase the tool “Digital well-being”, from Android operating systems - aiming at a more gradual change in the consumption of smartphones. As a result, a usability test was obtained, indicating a satisfactory potential use of the developed proposal.